(untitled) (Fiep Bulletin - online, 2011)
According to the United Nations there are at least four million people worldwide with Parkinson’s disease. It is estimated that this number will double by 2040, with the increasing elderly population. This research aimed to identify the combined effects of Reflexology with conventional treatment in patients with Parkinson’s disease. It was held in Paraná Association of People with Parkinsonism in the city of Curitiba-PR, Brazil, after prior authorization of the institution and 6 patients who participated in the survey. As for data collection, primarily patients with Parkinson answered a questionnaire after the first application of massage and Reflexology, after 10 days of application. The results were analyzed by Exel for Windows software and the realization of correlations and discussions from the findings and literature available. The results after every session of attendance: the patients felt well-being, calm 67%, 17% relaxation, 83% reduction in pain, 80% improvement in insomnia, 73% improvement in constipation, 68% improvement in memory; 90% improvement in speech and 85% improvement in swallowing 72% improvement in their movements, 70% improvement in bradykinesia, 78% improvement in mood and 70% reduction in spasms, 76% more disposition to leisure time, 88% more to ease dressing and 74% more motivation to exercise. It is concluded that foot reflexology can have beneficial results, combined with conventional treatment in patients suffering from Parkinson’s disease, improving activities of daily living and reducing adverse reactions of other treatments.